If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 = -3x + 4 Reorder the terms: -13 = 4 + -3x Solving -13 = 4 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -13 + 3x = 4 + -3x + 3x Combine like terms: -3x + 3x = 0 -13 + 3x = 4 + 0 -13 + 3x = 4 Add '13' to each side of the equation. -13 + 13 + 3x = 4 + 13 Combine like terms: -13 + 13 = 0 0 + 3x = 4 + 13 3x = 4 + 13 Combine like terms: 4 + 13 = 17 3x = 17 Divide each side by '3'. x = 5.666666667 Simplifying x = 5.666666667
| .75(x+40)=.35(x+20)+.35(x+20) | | 14/(x-3) | | 4=-1+x(2) | | x/62=22.2/29 | | -1382+719= | | 1.25+x=-5.25 | | 17/100=x/51 | | 12/3s=6 | | 20x+35=40x+75 | | 8(v+931)=208 | | 6x+28+2x=68 | | 3-24b=75 | | 3x-5/5 | | y=2.3x-20.7 | | 10x^2/x^2 | | 8x-2=-98 | | -7p+3+8p=7 | | 9+2x=-5y | | 1.48-(-2f)=0.2 | | 2,4=t/4.5 | | 1-7/13 | | 2/100=x/68 | | -8x-6+3x=7+4x-9 | | 5u+16=101 | | -3/2x-9=-27 | | y=33x-216 | | 2x-1=6+3 | | C/8-(-12)=12 | | 0.6=-2(m+9.1) | | 21x+6+x=180 | | v=u-8 | | X/5=76 |